2009
DOI: 10.1111/j.1574-6968.2009.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and translocation of a multiple antibiotic resistance region of aPsychrobacter psychrophiluspermafrost strain

Abstract: A Psychrobacter psychrophilus strain resistant to tetracycline and streptomycin was isolated from a 15,000-35,000-year-old permafrost subsoil sediment sampled from the coast of the Eastern-Siberian Sea. The genes conferring antibiotic resistance were localized on an c. 30-kb pKLH80 plasmid. It was shown that the antibiotic resistance region of this plasmid has a mosaic structure and contains closely linked streptomycin resistance (strA-strB) and tetracycline resistance [tetR-tet(H)] genes, followed by a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
(46 reference statements)
2
29
0
Order By: Relevance
“…The gene pair strA-strB is widespread in bacteria associated with plants, humans, and animals, including bacteria from Ͼ15,000-year-old permafrost sediments (41,44). When strA and strB are cloned separately, strB is not expressed because of a secondary structure barrier to the Shine-Dalgarno sequence and start codon (10), a finding consistent with our observations that nonsynonymous changes in strA also affect the phenotype caused by strB.…”
supporting
confidence: 80%
“…The gene pair strA-strB is widespread in bacteria associated with plants, humans, and animals, including bacteria from Ͼ15,000-year-old permafrost sediments (41,44). When strA and strB are cloned separately, strB is not expressed because of a secondary structure barrier to the Shine-Dalgarno sequence and start codon (10), a finding consistent with our observations that nonsynonymous changes in strA also affect the phenotype caused by strB.…”
supporting
confidence: 80%
“…Together they form the plasmid backbone region. The accessory region of the pKLH80 plasmid contains five antibiotic resistance genes: previously characterized genes, strA-strB and tetRtet(H) (Petrova et al, 2009), and an additional gene discovered in this work, bla RTG . Two IS elements, ISAba14 and ISPsma1, were also found in this region, in addition to ISPpy1 identified previously (Petrova et al, 2009(Petrova et al, , 2013.…”
Section: Resultsmentioning
confidence: 90%
“…Detailed analysis of the vancomycin resistance gene cluster in this metagenome revealed conservation of gene sequence and synteny with modern resistance clusters in the clinic as well as protein function and structure. Other studies have shown the presence of resistance genes in Siberian permafrost (Petrova et al 2009) and showed working resistance genes from at least 5000 years ago using functional metagenomics (Perron et al 2015). Isolated instances of resistance genes in human commensals and pathogens have also been documented.…”
Section: Links To the Environment And Gene Mobilizationmentioning
confidence: 97%